2019
DOI: 10.3390/en12020295
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of European Union Countries

Abstract: This study utilizes the dynamic data envelopment analysis (DEA) model by considering time to measure the energy environmental efficiency of 28 countries in the European Union (EU) during the period 2006–2013. There are three kinds of variables: input, output, and carry-over. The inputs are labor, capital, and energy consumption (EC). The undesirable outputs are greenhouse gas emissions (GHE) and sulfur oxide (SOx) emissions, and the desirable output variable is gross domestic product (GDP). The carry-over vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The abovementioned wastewater discharge (WD), COD, other major pollutants (OMP) are bad outputs. We refer to Hsieh et al and Ma et al [26,27] to adjust bad outputs, as good output variables, and utilize the maximum emission value of each bad output in all DMUs as the base; whereby the adjustment value equals (maximum value of DMUs -original emissions value of each DMU) + 1 to become good outputs. These results illustrate the relationships among rapid economic growth, water resources' use policy, and environmental degradation in China at the provincial level, thus spurring local governments to make a careful assessment of appropriate related policies when actively targeting economic development at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned wastewater discharge (WD), COD, other major pollutants (OMP) are bad outputs. We refer to Hsieh et al and Ma et al [26,27] to adjust bad outputs, as good output variables, and utilize the maximum emission value of each bad output in all DMUs as the base; whereby the adjustment value equals (maximum value of DMUs -original emissions value of each DMU) + 1 to become good outputs. These results illustrate the relationships among rapid economic growth, water resources' use policy, and environmental degradation in China at the provincial level, thus spurring local governments to make a careful assessment of appropriate related policies when actively targeting economic development at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [69] argued that fixed asset stock is a significant indicator of environmental efficiency and should be adopted as a carry-over indicator to identify the performance gap among decision-making units. Inspired by Li et al [69,70] and Hsieh et al [71], the study adopts fixed assets as a carry-over indicator. As shown in Table 8, fixed assets adjustment values are negative for all investigated African countries except for Togo and Namibia's efficient countries.…”
Section: Ecological Efficiency Improvements In Africa From 2010 To 2016mentioning
confidence: 99%
“…Cui et al (2014) found that energy efficiency is mostly driven by investments into energy technologies research and tax exemptions for technology companies [45]. Based on the analysis of 28 European countries, Hsieh et al (2019) recommend that "the EU's strategy for environmental energy improvement should be to pay attention to the benefits of renewable energy utilization, reducing GHG emissions, and enhancing the development of renewable energy utilization to help achieve the goal of lower GHG emissions" [48]. Apergis et al (2015) show that capital-intensive countries are more energy efficient than labor-intensive ones [34].…”
Section: Literature Review-energy-related Country Comparisons With Damentioning
confidence: 99%
“…Out of the 25 studies analyzed (including the present one), 15 of them (60%) use the same set of inputs: labor force, capital stock and energy consumption [34,39,40,42,44,[47][48][49][50][52][53][54]56,57,59]. Furthermore, out of these 15 studies, four consider only the GDP as an output [44,49,53,56], while the rest consider the GDP as a desirable output and GHG emissions as an undesirable output [34,39,40,42,47,48,50,52,54,57,59]. Within DEA country comparisons, efficiency is, therefore, usually measured as a minimization of the labor force, capital stock, and energy consumption (inputs) in order to maximize the GDP (desirable output) and minimize the GHG emissions (undesirable output).…”
Section: Literature Review-energy-related Country Comparisons With Damentioning
confidence: 99%